2020
DOI: 10.1136/bmjopen-2020-040857
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing palliative care referral for hospitalised patients with heart failure: an exploratory, randomised, multi-institutional survey of hospitalists and cardiologists

Abstract: ObjectiveTo identify factors influencing cardiologists’ and hospitalists’ decisions regarding palliative care referral among hospitalised patients with advanced heart failure.DesignAn exploratory, randomised vignette-based survey.SettingCardiology and hospitalist divisions at three Michigan State institutions and the Society of Hospital Medicine’s Michigan Chapter.Participants145 hospitalists and 64 cardiologists.Outcome measuresPrimary outcomes included participants’ reports of their likelihood of referring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The reduction in daily medical costs confirmed that cost reduction was not solely due to shorter LOS. However, there has been great variability in the practice patterns of hospitalists worldwide [19,20]. In addition, the learning curve, experience, and available support of hospitalist teams may influence the process and utilization of aggressive intensive care [21].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in daily medical costs confirmed that cost reduction was not solely due to shorter LOS. However, there has been great variability in the practice patterns of hospitalists worldwide [19,20]. In addition, the learning curve, experience, and available support of hospitalist teams may influence the process and utilization of aggressive intensive care [21].…”
Section: Discussionmentioning
confidence: 99%
“…Reliability was assessed using Cronbach’s α (>0.6) ( 44 ). Convergent validity was assessed using the average variance extracted (AVE > 0.36) and composite reliability (CR > 0.6) for all constructs ( 20 ). Discriminant validity was tested using the Fornell–Larcker criterion.…”
Section: Methodsmentioning
confidence: 99%
“…A range of patient-, provider- and system- related factors contribute to non-referrals, late or crisis referrals to palliative care for patients with chronic HF and chronic respiratory disease. Patients and families have identified denial, misperception about the potential benefits and purpose of palliative care, and negative previous experiences with services ( 20 , 21 ). While some providers report feeling comfortable providing a palliative approach ( 22 ), for others there is uncertainty about the role of palliative care and when this approach should be introduced ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some providers report feeling comfortable providing a palliative approach ( 22 ), for others there is uncertainty about the role of palliative care and when this approach should be introduced ( 23 , 24 ). Health care providers' poor recognition of their patient's palliative care needs can be impacted by time constraints, a lack of education or training, and awareness or availability of standardized tools and referral pathways ( 20 , 22 25 ). Some health care providers perceive palliative care is not as useful for non-malignant conditions or that SPC services prioritize patients with cancer ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation